THE INFLUENCE OF SOCIAL MEDIA AND BRAND EQUITY ON CUSTOMER LOYALTY IN MALANG CLOTHING AND DISTRO INDUSTRY - Nizami, Aris Mukti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
In this digital era, every aspect of human life is almost dependable on the technology and internet. Social media is one of the global phenomenon that embrace several aspects of human life into one dimension. This combined with the science of marketing strategy, has developed a mutual relation that enhances the performance of the company’s ability. The internet and social media has created marketing strategy into a new level by introducing a cheap yet effective tool to gain effective market by introducing their brand equity into customer with amazing results. Brand equity, such as brand awareness, brand trust , and perceived value is one of the main drives for a customer to become a loyal. A company should understand this matter as loyal customer is one of the most precious things that company should have. By having loyal customer, the repeated purchase intention can be made , which will give extra benefit to the company. Combining brand equity with effectiveness of social media marketing, it become powerful methods as marketing strategy, especially in the business that attracted by young customer. Distro, or distribution store in Malang, is one of the company that adapting a new marketing strategy each period. Powered by young generation and young leader, many distro distinguish themselves by having dynamic and interesting marketing strategy. In this study, there will be explanation all of this social media , brand equity and brand loyalty phenomenon that happen in distro marketing strategy. The analysis will be using multiple regression analysis method, which aided by SPSS program on windows. Finding of this research prove that social media and brand equity have significant impact on the customer loyalty, which give reader insight how important social media marketing and brand equity is.Keywords : Social media, brand awareness, brand trust, perceived value, customer loyalty, distro